Jawabanmu

2014-06-19T07:38:59+07:00
√3tanxsinx = √3Sin²x/cosx =sinx√3/cosx  dan 1-cosx = 2sin²(1/2)x
L i m  √3tanxsinx = L i m sinx√3/cosx . x . (x/2)²
x⇒0    1 - cosx       x⇒0    2sin²(1/2)x  x   (x/2)²
                           = L i m Sinx  .  (x/2)²   .  x√3/cosx
                              x⇒0    x    sin²(1/2)x    2x²/4
                           = L i m 2√3/cosx
                              x⇒0      x²
                           = 2√3/Cos0
                                  0²
                           = 2√3
                                 0
                           = ∞  (tak terdefinisi)
1 1 1